Quality Evaluation of Traditional Chinese Medicine Mylabris Based on Heavy Metal Risk Assessment and Analysis of Pharmacological Component Contents. Issue 2 (16th January 2023) - Wu, Faming; Peng, Jie; Ran, Junfeng; Tian, Yubo; Li, Xiang; Ren, Yan; Gai, Rongyin; Zhang, Yunying
Abstract: As a highly representative traditional Chinese anti‐tumor medicinal material, the biomass of Mylabris is collected from the wild. However, the living environments of Mylabris is differ, so Mylabris may be contaminated by heavy metal pollution depending on the environment. These environments may also affect the amount of biosynthesis of its medicinal ingredient, cantharidin, there by affecting the quality of Mylabris. In this study, we determined the heavy metal content in Mylabris from different origins by using ICP‐MS, evaluated the risk posed by these heavy metals, and recommended theoretical maximum limits of heavy metals in medicinal Mylabris. The results show that the Cu content in Mylabris is substantially higher than that in Cr, As, Pb, Cd, and Hg. A quantitative risk assessment showed that Mylabris poses no noncarcinogenic risks. The results of the total carcinogenic risk value showed that origins S12 and S13 pose carcinogenic risk by Cr and As, and the rest of the origins were in the human‐tolerable carcinogenic risk range. We found large differences in the cantharidin content in Mylabris from different origins. In general, the Mylabris from origins S2, S3 and S4 had a higher in vivo cantharidin content, which proved that the quality of the medicinal materials was higher here than in other production areas. Finally, we providing a reference for the quality evaluation of medicinal Mylabris materials. Abstract :